Unveiling the hidden reserves: allocation strategies associated with underground organs of Cerrado legumes in fire-prone savannas - Cozin, Bruno Bonadio [UNESP]; Ferreira, Tassia Caroline [UNESP]; Daibes, L. Felipe [UNESP]; de Carvalho, Isabella Fiorini [UNESP]; dos Santos, Beatriz Silvério [UNESP]; de Souza, Roberta Possas [UNESP]; de Camargos, Liliane Santos [UNESP]; Martins, Aline Redondo [UNESP] (CSIRO Publishing, 2024)
The synthesis and differential allocation of reserve compounds is an important adaptive mechanism that enables species to resprout in fire-prone ecosystems. The analysis of compound allocation dynamics (differential accumulation of compounds between plant organs) provides insights into plant responses to disturbances. The aim was to quantify reserves in eight legume species from Cerrado open savannas with high fire frequency in order to investigate the patterns of allocation and distribution of compounds between leaves and underground organs, drawing ecophysiological inferences. The species were collected in ‘campo sujo’ areas of the Cerrado. Leaves and underground organs (xylopodium, taproot tubers) were subjected to physiological analyses. Overall, underground organs were characterised by greater deposits of carbohydrates, mainly soluble sugars, and also with the accumulation of proteins and amino acids. This suggests that nitrogen reserves, as well as carbohydrates, may have an ecophysiological function in response to fire, being allocated to the underground organs. Phenols were mainly evident in leaves, but a morphophysiological pattern was identified, where the two species with taproot tubers tended to concentrate more phenols in the underground portion compared to species with xylopodium, possibly due to functional differences between these organs. Such data allow inferring relevant ecophysiological dynamics in legumes from open savannas.
Keywords: allocation; carbon compounds; Cerrado; ecophysiology; leaves; nitrogen compounds; taproot tuber; xylopodium